Genomic analysis reveals depression due to both individual and maternal inbreeding in a free‐living mammal population. Issue 13 (6th June 2016) - Bérénos, Camillo; Ellis, Philip A.; Pilkington, Jill G.; Pemberton, Josephine M.
Abstract: There is ample evidence for inbreeding depression manifested as a reduction in fitness or fitness‐related traits in the focal individual. In many organisms, fitness is not only affected by genes carried by the individual, but also by genes carried by their parents, for example if receiving parental care. While maternal effects have been described in many systems, the extent to which inbreeding affects fitness directly through the focal individual, or indirectly through the inbreeding coefficients of its parents, has rarely been examined jointly. The Soay sheep study population is an excellent system in which to test for both effects, as lambs receive extended maternal care. Here, we tested for both maternal and individual inbreeding depression in three fitness‐related traits (birthweight and weight and hindleg length at 4 months of age) and three fitness components (first‐year survival, adult annual survival and annual breeding success), using either pedigree‐derived inbreeding or genomic estimators calculated using 37 000 SNP markers. We found evidence for inbreeding depression in 4‐month hindleg and weight, first‐year survival in males, and annual survival and breeding success in adults. Maternal inbreeding was found to depress both birthweight and 4‐month weight. We detected more instances of significant inbreeding depression using genomic estimators than the pedigree, which is partly explained through the increased sample sizes available. In conclusion, our results highlight that cross‐generational inbreeding effects warrant further exploration in species with parental care and that modern genomic tools can be used successfully instead of, or alongside, pedigrees in natural populations.